Clearing the land with an animal-drawn cutter - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1987)
Clearing the land with an animal drawn cutter A new animal-drawn roller knife cutter to clear grass and crop residues has been developed by the Promotion of Adapted Farming Systems Based on Animal Traction project in Cameroon. This cutter is easy to...